EVALUASI WASTE MATERIAL PADA PROYEK BERBASIS KONSEP GREEN CONSTRUCTION DAN PROYEK KONVENSIONAL - Rachmawati Edy Lestari; Khanif Ragil Pamungkas; Arif Hidayat; Frida Kistiani (Jurnal Karya Teknik Sipil, 2013)
The fact that construction causes negative impact to the environment such as degradation of environmental quality that caused by the increasing of waste volume produced by construction activity. Based by research around the globe, it is said that more than 50% of waste are produced by construction activity (Wulfram Ervianto, 2012). The increasing of construction waste comes from a construction process. If large amount of construction waste produced, so analogically the natural resources that exploitated has a large of amount of volume either. So it needs a right management to overcome by appliying a responsible construction process so that the waste that produced will be decreased. In its development, that construction process is known as green construction. This research will discuss about the comparison between the amount of waste that produced during the processing of the 1st and 2nd floor of upper structure work between green construction and conventional project based on implementation method applied by each project. Research method used such that qualitative method with description and data derivation by direct observation and interview on field with case study of construction project of Mataram City Yogyakarta Hotel and Apartment with PT. Pembangunan Perumahan (Persero) contractor as an object of green construction project and Hotel 101 Yogyakarta one with PT. Bintang Sewu Sejahtera as an object of conventional project. From the observation result, the fact that waste on green construction project is considerably less than conventional is obtained, that is with percentage of bar reinforcement waste 0.54%, wood/plywood 4.85%, and concrete 0%.  It shows that selecting the implementation method and waste management precisely can decrease material solid waste.